Development of Science Teaching Modules in Class IV Elementary School Independence Curriculum - Urip Umayah (Tinta Emas Publisher, 2023)
Research on the development of science teaching modules and data processing is designed to be more practical, effective, and easy to understand for fourth grade elementary school students using the ADDIE model development method. The types of data in this study were: content validation, design validation, student and teacher response questionnaires, and written tests of learning outcomes. The analysis technique uses descriptive analysis then the data is processed by being converted using a predetermined formula. The results of content validation from experts after being converted to the achievement level table obtained 89.09%. The design validation results from experts after being converted with the achievement level table obtained 86.49%. The results of field trials after being converted with the achievement level table obtained 91.81%. While the written test results obtained completeness of 29 children with a percentage of 90.625% of 32 children. From the data and analysis that has been done, it can be concluded that the results of the development of the IPAS teaching module for grade IV Semester II Elementary Schools can be used as a teaching module